История Древнего Востока (1988)
Kuziš?in, V.l. (Ed.), Geschichte des Alten Orients; S.92-282: Altes Vorderasien und Iran: M.A. Dandamaev, S.S. Solov'jeva, D.G. Reder, V.l. Kuziš?in, V.M. Masson, A.A. Vigasin